Internet and Crimes: How the Law Responds to Internet Based Crimes? A Book Review of "Aspek Hukum Penipuan Berbasis Internet", Maskun & Wiwik Meilarati, CV Keni Media, Makassar, 2016, 238 Pages, ISBN 978-602-74375-5-5 - Lemuel, Yehezkiel (JILS (Journal of Indonesian Legal Studies), 2019)
Various internet crimes such as cyberstalking, internet fraud, website scam, cyber aggression, cyber espionage, and child pornography are new types of crime that have evolved from various types of conventional crimes such as fraud and theft which previously could only be done physically have been switched by using only the internet. This book is expected to be academically useful for undergraduate students and the general public who want to find out about cybercrime and internet fraud specifically. With this kind of situation, it is needed a strong legal basis of law to not just ensure the people's comfort and safety in using the internet but also to crack down the perpetrators assertively so that this action will not be repeated in the future.